Romantische Lieder - Hesse, Hermann, 1877-1962 (Salt Lake City, UT : Project Gutenberg, 2014)
"Romantische Lieder" by Hermann Hesse is a poetry collection published in 1898/1899. It was Hesse's first published book, appearing before his later fame with "Peter Camenzind." The poems reflect the strong influence of German Romantic poets like Brentano, Eichendorff, and Novalis, making this collection an exemplary work of the Neoromantic literary movement. Though commercially unsuccessful at first, with only 54 copies sold from an initial printing of 600, the collection represents Hesse's early artistic development. (This is an automatically generated summary.)
Wikipedia page about this book: https://de.wikipedia.org/wiki/Romantische_Lieder
Release date is 2014-06-29
Produced by Jens Sadowski
Keywords: Poetry